2013
DOI: 10.1371/journal.pone.0080296
|View full text |Cite
|
Sign up to set email alerts
|

Combining Biochemical and Imaging Markers to Improve Diagnosis and Characterization of Mild Traumatic Brain Injury in the Acute Setting: Results from a Pilot Study

Abstract: BackgroundMild traumatic brain injury (mTBI) is a significant healthcare burden and its diagnosis remains a challenge in the emergency department. Serum biomarkers and advanced magnetic resonance imaging (MRI) techniques have already demonstrated their potential to improve the detection of brain injury even in patients with negative computed tomography (CT) findings. The objective of this study was to determine the clinical value of a combinational use of both blood biomarkers and MRI in mTBI detection and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 70 publications
4
74
0
Order By: Relevance
“…Mounting evidence demonstrates the microstructural damage in patients with mTBI. 8,[70][71][72][73] Our pilot data suggest that, in response to microstructural damage on the cingulate bundle shown on DTI, other regions of the brain tend to have higher FC with the anterior cingulate cortex on resting state fMRI signal. 74 This suggests a compensatory mechanism of brain injury.…”
Section: Limitation and Future Workmentioning
confidence: 73%
“…Mounting evidence demonstrates the microstructural damage in patients with mTBI. 8,[70][71][72][73] Our pilot data suggest that, in response to microstructural damage on the cingulate bundle shown on DTI, other regions of the brain tend to have higher FC with the anterior cingulate cortex on resting state fMRI signal. 74 This suggests a compensatory mechanism of brain injury.…”
Section: Limitation and Future Workmentioning
confidence: 73%
“…This study compared the acute time course of GFAP and UCH-L1 biomarkers using proprietary sandwich ELISA 11,14 for astrocyte and neuronal pathology, respectively in a model of moderate parasagittal fluid percussion TBI in rats. Levels of GFAP were significantly elevated in serum at 3 and 6 hours after TBI compared to baseline and time-matched sham-TBI animals while UCH-L1 was significantly elevated in serum only at 3 hours after TBI.…”
Section: Discussionmentioning
confidence: 99%
“…Work by Kou et al examined serum in combination with imaging biomarkers and showed that glial biomarkers correlated with presence of intracranial hemorrhages detected with susceptibilityweighted imaging, while abnormal FA and WM volumes were correlated with impaired neurofunctional status (181). A recent pilot study using a multifeature classification algorithm showed that a multimodal evaluation achieved higher accuracy than the best single metric in differentiating mTBI patients from control subjects (76).…”
Section: State Of the Art: Mr Imaging Applications In Mild Traumatic mentioning
confidence: 99%